A SIRPαFc Fusion Protein Conjugated With the Collagen-Binding Domain for Targeted Immunotherapy of Non-Small Cell Lung Cancer - Liu, Jiayang; Meng, Zhefeng; Xu, Tongyang; Kuerban, Kudelaidi; Wang, Songna; Zhang, Xuyao; Fan, Jiajun; Ju, Dianwen; Tian, Wenzhi; Huang, Xuan; Huang, Xiting; Pan, Danjie; et al. (Frontiers in Immunology, 2022)
SIRPαFc fusion protein can block immunosuppressive CD47-SIRPα signal between macrophages and tumor cells as a decoy receptor and has been demonstrated its immunotherapeutic efficacy in various tumors. However, its clinical application was limited because of the potential hematologic toxicity. The heptapeptide “TKKTLRT” is a collagen-binding domain (CBD) which can bind collagen specifically. Herein, we aim to improve the tumor targeting of SIRPαFc, therefore avoid its unnecessary exposure to normal cells through synthesizing a TKKTLRT-SIRPαFc conjugate. Experiments at molecular and cellular levels indicate that the TKKTLRT-SIRPαFc conjugate derived collagen-binding affinity, and the introduction of CBD did not impact the CD47-binding affinity as well as its phagocytosis-promoting effect on NSCLC cells. In vivo distribution experiments showed that CBD-SIRPαFc accumulated in tumor tissue more effectively compared to unmodified SIRPαFc, probably due to the exposed collagen in tumor vascular endothelium and stroma resulting from the abnormal vessel structure. On A549 NSCLC nude mice xenograft model, CBD-SIRPαFc presented more stable and effective anti-tumor efficacy than SIRPαFc, along with significantly increased CD11b+F4/80+ macrophages especially MHC II+ M1 macrophages within tumors. All of these results revealed that CBD brought tumor targeting ability to SIRPαFc fusion protein, which contributed to the enhanced anti-tumor immune response. Altogether, the CBD-SIRPαFc conjugate may have the potential to be an effective tumor immunotherapy with improved anti-tumor efficacy but less non-tumor targeted side effect.